L’uso delle strategie di trasparenza nella comunicazione dei docenti plurilingui - Monami, Elena (Incontri. Rivista europea di studi italiani, 2022)
The use of transparency strategies in the communication of plurilingual teachersThe aim of this article is to present and discuss the nature and role of transparency strategies in the communication of plurilingual teachers in classes of Italian as a foreign language. Our research questions intend to deepen two key concepts strictly connected to teacher talk:• What are the most used transparency strategies by plurilingual teachers of Italian as a foreign language?• What is the frequency of use of such transparency strategies in relation to CEFR competence levels?Our quantitative and qualitative analysis is data-driven and is based on the CLODIS corpus (oral language of teachers of Italian for foreigners), which collects interactions in over 150 L2 Italian classes and represents a link between theoretical study and its teaching applications.